PELAPISAN NIKEL PADA PELAT TEMBAGA DENGAN WAKTU 5, 10 DAN 15 MENIT DAN KOMPOSISI NIKEL KLORID 50 GRAM, 60 GRAM DAN 70 GRAM - Waluyo, Joko; Huda, Saiful; wuryanto, Toto Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
Electroplating is plating of metal on the metal or something has conductor charateristic by aiding direct current (DC) of electricity in the electrolyte solution function as metal ions solvent media, so it gives performance and smoothness that is interesting on the metal surface. The aim of this research is to know the plating result quality by using the difference chloride nickel composition. The are 50 gramn 60 gram and 70 gran of NiCL with plating duration 5 minutes, 10 minutes and 15 minutes, on the material with dimension 100 mmx70mm with thickness 3 mm. Plating process is done in the trapezium solution reservoir tank or called by Hull Cell. The result of this research is obtained that the best composition is 70 gran NiCl, with 15 A/dm2 current dense and with 15 minutes plating duration, the highest hardness value= 188.5 VHN and the lowest = 71.1 VHN, the highgest thicknees = 53.84 µm and the lowest = 3.07 µm, the best fltnees with value of Ra= 0.0573 µm, Rz = 0.400 µm and R max = 0.4500 µm and the worst flatness with the value of Ra = 0.4723 µm, Rz = 3.8250 µm and R max = 4.500 µm whereas the highest result glossy result = 72 % and the lowest = 33 %.